Sex- and age-related differences in the inflammatory properties of cardiac fibroblasts: impact on the cardiosplenic axis and cardiac fibrosis - Pappritz, Kathleen; Puhl, Sarah-Lena; Matz, Isabel; Brauer, Erik; Shia, Yi Xuan; El-Shafeey, Muhammad; Koch, Suzanne E.; Miteva, Kapka; Mucha, Christin; Duda, Georg N.; Petersen, Ansgar; Steffens, Sabine; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Age and sex are prominent risk factors for heart failure and determinants of structural and functional changes of the heart. Cardiac fibroblasts (cFB) are beyond their task as extracellular matrix-producing cells further recognized as inflammation-supporting cells. The present study aimed to evaluate the impact of sex and age on the inflammatory potential of cFB and its impact on the cardiosplenic axis and cardiac fibrosis. Materials Left ventricles (LV) of 3- and 12-months old male and female C57BL/6J mice were harvested for immunohistochemistry, immunofluorescence and cFB outgrowth culture and the spleen for flow cytometry. LV-derived cFB and respective supernatants were characterized. Results LV-derived cFB from 3-months old male mice exhibited a higher inflammatory capacity, as indicated by a higher gene expression of CC-chemokine ligand (CCL) 2, and CCL7 compared to cFB derived from 3-months old female mice. The resulting higher CCL2/chemokine C-X3-C motif ligand (Cx3CL1) and CCL7/Cx3CL1 protein ratio in cell culture supernatants of 3-months old male vs. female cFB was reflected by a higher migration of Ly6Chigh monocytes towards supernatant from 3-months old male vs. female cFB. In vivo a lower ratio of splenic pro-inflammatory Ly6Chigh to anti-inflammatory Ly6Clow monocytes was found in 3-months old male vs. female mice, suggesting a higher attraction of Ly6Chigh compared to Ly6Clow monocytes towards the heart in male vs. female mice. In agreement, the percentage of pro-inflammatory CD68+ CD206− macrophages was higher in the LV of male vs. female mice at this age, whereas the percentage of anti-inflammatory CD68+ CD206+ macrophages was higher in the LV of 3-months old female mice compared to age-matched male animals. In parallel, the percentage of splenic TGF-β+ cells was higher in both 3- and 12-months old female vs. male mice, as further reflected by the higher pro-fibrotic potential of female vs. male splenocytes at both ages. In addition, female mice displayed a higher total LV collagen content compared to age-matched male mice, whereby collagen content of female cFB was higher compared to male cFB at the age of 12-months. Conclusion Age- and sex-dependent differences in cardiac fibrosis and inflammation are related to age- and sex-dependent variations in the inflammatory properties of cardiac fibroblasts.